2016
DOI: 10.1039/c6fo00656f
|View full text |Cite
|
Sign up to set email alerts
|

The wild Egyptian artichoke as a promising functional food for the treatment of hepatitis C virus as revealed via UPLC-MS and clinical trials

Abstract: Infection by hepatitis C virus (HCV) and its subsequent complications are a major cause of mortality worldwide. The water extract of the wild Egyptian artichoke (WEA) (Cynara cardunculus L. var. sylvestris (Lam.) Fiori) leaves is a freely available herbal product that is used for treatment of HCV-infection complications such as jaundice and ascites. The purpose of this study was to evaluate whether WEA exhibits activity against HCV, identify bioactive chemicals in its extract and to tentatively examine the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…None of these studies, testing a high concentration of BPF, reported any type of adverse events. In a study carried out in individuals infected by hepatitis C virus, CyC extract normalized ALT and AST, as well as the level of bilirubin (49). Furthermore, only a moderately interaction with human drug-metabolizing enzymes, such as CYP1A2, CYP2D6, CYP2E1, and CYP3A4, was observed (50).…”
Section: Discussionmentioning
confidence: 98%
“…None of these studies, testing a high concentration of BPF, reported any type of adverse events. In a study carried out in individuals infected by hepatitis C virus, CyC extract normalized ALT and AST, as well as the level of bilirubin (49). Furthermore, only a moderately interaction with human drug-metabolizing enzymes, such as CYP1A2, CYP2D6, CYP2E1, and CYP3A4, was observed (50).…”
Section: Discussionmentioning
confidence: 98%
“…The wild Egyptian artichoke exhibited promising activity against HCV (Elsebai et al, 2016a) which were related to its sesquiterpene lactones especially cynaropicrin (Elsebai et al, 2016b). Cynaropicrin demonstrated outstanding activity against HCV since, for the first time, the performed in vitro studies showed that cynaropicrin has potent and broad spectrum activity as a cell-entry inhibitor against all genotypes of HCV with EC 50 in the low micromolar range (Elsebai et al, 2016b).…”
Section: Anti-hepatitis C Virus (Anti-hcv) Activitymentioning
confidence: 99%
“…Examples of herbal medicines targeting for inhibition of HCV entry include methanolic extracts of Bupleurum kaoi root, 36 Morinda citrifolia and Rhizoma coptidis, 37,38 ethanol extracts of fruits of Schisandra sphenanthera Rehd. et Wils, 39 water extracts of wild Egyptian artichoke, 52 and other extracts of Dipsacus asperoides, 40 Magnolia officinalis (Hou-Pu), 30 and compounds of epigallocatechin-3-gallate, delphinidin, 41 flavone and flavanbased compounds (amentoflavone, 7,40-dihydroxyflavanone, and orobol). 42 Others NS protein inhibition and HCV entry inhibition are the two main anti-HCV modes of herbal medicines.…”
Section: Hcv Entry Inhibitionmentioning
confidence: 99%